1988
DOI: 10.1051/rnd:19880903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactose hydrolysis on calcium absorption during duodenal milk perfusion

Abstract: Summary. A multi-lumen intubation system was used to study the absorption of calcium, glucose and galactose in 13 human subjects. The intubation was placed between the duodenum abdomen and proximal jejunum and the subjects were perfused with milk and lactase-supplemented milk. Lactose disappearance over a 20 cm length of intestine was used as the index of lactase activity. The subjects were assigned to one of two groups, lactase-normal and lactase-deficient.There was linear correlation between the absorption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…These findings indicate that hydrolysis of lactose in the intestine is a prerequisite for increased Ca absorption. In keeping with this, Birlouez-Aragon (1988) showed that after milk consumption lactose-intolerant subjects absorb less Ca than lactose-tolerant subjects. Furthermore, compared with normal milk, lactase-treated milk enhanced Ca absorption in lactose-intolerant subjects but had no effect in lactose-tolerant subjects (Birlouez-Aragon, 1988).…”
Section: Discussionsupporting
confidence: 52%
“…These findings indicate that hydrolysis of lactose in the intestine is a prerequisite for increased Ca absorption. In keeping with this, Birlouez-Aragon (1988) showed that after milk consumption lactose-intolerant subjects absorb less Ca than lactose-tolerant subjects. Furthermore, compared with normal milk, lactase-treated milk enhanced Ca absorption in lactose-intolerant subjects but had no effect in lactose-tolerant subjects (Birlouez-Aragon, 1988).…”
Section: Discussionsupporting
confidence: 52%
“…Two‐way transport systems in the intestinal absorption of calcium are considered: passive transport in the duodenum to ileum and diffusion transport in the jejunum. There are various hypotheses concerning the calcium absorption‐promoting action of lactose: It has been reported that lactose increased calcium permeability in small intestinal villi (18), an increase in intestinal lactic acid bacteria decreased intestinal pH and promoted calcium absorption (32, 33), and lactose formed chelates or complexes (34), but many points remain unclear regarding the mechanisms. Previously, we reported that intestinal alkaline phosphatase activity in the rat intestine was markedly enhanced after 21 days of being fed a 10% lactose diet, and lactose is one of the factors responsible for intestinal alkaline phosphatase activity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Lactose stimulates the intestinal absorption of calcium in the infant because in these subjects, the enzyme β-galactosidase (which hydrolyses lactose into galactose and glucose) is highly expressed. Some studies in fact demonstrated that β-galactosidase-deficient subjects absorbed less calcium than β-galactosidase-normal subjects because are the hydrolytic products of β-galactosidase (glucose and galactose) that promote the calcium absorption [31,32]. Therefore, even after weaning, if a balanced diet is followed, donkey milk favors bones mineralization.…”
Section: Donkey Milk and Its Affinity With Human Milkmentioning
confidence: 99%